Reactivation of pulmonary tuberculosis during cancer treatment. Issue 4 (December 2015) - Jacobs, Ramon E.A.; Gu, Ping; Chachoua, Abraham
Abstract: Reactivation of Mycobacterium tuberculosis can occur in patients with latent tuberculosis (TB) with risk factors including chronic disease (i.e., malignancy). We herein describe the case of an immigrant from Hong Kong with lung cancer and no known TB disease who presents with reactivation of TB in the setting of chemotherapy and radiation therapy.